Implementation of Live Worksheets Assisted Interactive Student Worksheets Based on Discovery Learning - Maysara Maysara; Dinny Ariana; Saefuddin Saefuddin; Aceng Haetami; Habiddin Habiddin (Postgraduate, University of Mataram, 2023)
This study aims to ascertain the learning outcomes, effectiveness, and significant differences between printed worksheets on electrolytic cell material and interactive student worksheets based on discovery learning. This research is in a quasi-experimental design with a pretest-posttest control group design. The research instrument consisted of multiple-choice test questions with research subjects in classes XII MIPA 6 and XII MIPA 8 at Public High School 1 Kendari. Data analysis techniques consisted of descriptive analysis and inferential analysis. According to the investigation's findings, students who used interactive student worksheets based on discovery learning and supported by Live Worksheets with printed student worksheets experienced increased post-test learning outcomes. Still, the increase in the experimental class was higher than in the control class. As a result, Live Worksheets-assisted interactive student worksheets based on discovery learning on electrolytic cell material are helpful in education because they can enhance student learning outcomes.